Electrical percolation during gelation of lithium doped siloxane-poly(oxyethylene) hybrids - Sacco, A. P.; Dahmouche, K.; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP] (Springer, 2004)
Gelation mechanisms of lithium-doped Siloxane-Poly(oxyethylene) (PEO) hybrids containing polymer of two different molecular weight (500 and 1900 g/mol) were investigated through the evolution of the electrical properties during the solgel transition. The results of electrical measurements, performed by in-situ complex impedance spectroscopy, were correlated with the coordination and the dynamical properties of the lithium ions during the process as shown by Li-7 NMR measurements. For both hybrids sols, a decrease of the conductivity is observed at the initial gelation stage, due to the existence of an inverted percolation process consisting of the progressive separation of solvent molecules containing conducting species in isolated islands during the solid network formation. An increase of conductivity occurs at more advanced stages of gelation and aging, attributed to the increasing connectivity between PEO chains promoted by the formation of crosslinks of siloxane particles at their extremities, favoring hopping motions of lithium ions along the chains.
Keywords: gelation mechanisms; electrical percolation; hybrid materials; ionic conductivity